A study on the left ventricular hypertrophy among the patients of chronic kidney disease stage third to five - Vankayala, Ashok; Behera, Kamal Lochan; Raju, D. S. S. K.; Sayana, Suresh Babu (International Journal of Research in Medical Sciences, 2019)
Background: In Chronic kidney Disease (CKD) a significant risk factor for mortality is Cardiovascular disease (CVD) and the most prevalent cardiovascular risk factor is left ventricular hypertrophy (LVH). Anemia, hypertension and volume overload are risk factors for LVH in CKD. So, the present was aimed at comparing the risk factors between CKD with and without LVH. Methods: A cross sectional study carried out over a 2 year period in Department Nephrology and General Medicine OPD, MIMS, Vizianagaram, Andhra Pradesh. A total of 120 patients are included in this study and divided in to CKD stage III to V based on estimated GFR. Based on 2D echocardiography data CKD cases are further divided in to CKD with LVH and CKD without LVH. Results: The Left ventricular mass index was significant higher in CKD with LVH (128.89±19.28) when compared with CKD without LVH (108.20±10.28). The left ventricular mass index was noted in more number in stage V of CKD. It is also observed that the left ventricular mass index was negatively correlated with haemoglobin and eGFR and was positively correlated with systolic blood pressure and serum NT-proBNP. Conclusions: Present study finding suggested that the incidence of LVH is higher in CKD patients. LVH was positively correlated with hypertension and NT-proBNP and negatively correlated with anemia and estimated GFR.